Musculoskeletal Point-of-Care Ultrasound for the Detection of Active Haemorrhage in Intramuscular Haematoma: A Case Report - Ahlam Alfahmi; Shahad Sheerah (The Journal of Medicine, Law & Public Health, 2025)
A 73-year-old man on chronic warfarin therapy presented to the emergency department with acute right thigh pain and swelling, without a history of trauma. Musculoskeletal point-of-care ultrasound (MSK-POCUS) rapidly identified an intramuscular hematoma with evidence of active hemorrhage. Subsequent computed tomography angiography (CTA) confirmed a sizable hematoma in the right vastus intermedius muscle and detected a small pseudoaneurysm. The patient was managed conservatively, with close monitoring yielding no further complications. This case demonstrates the diagnostic utility and efficiency of MSK-POCUS in the acute evaluation of musculoskeletal complaints, particularly in patients at risk for anticoagulant-induced bleeding. The report highlights the value of bedside ultrasound for prompt diagnosis, its advantages over other imaging modalities in emergency settings, and the importance of enhancing training for widespread POCUS implementation in clinical practice.